Social skills, financial literacy, fitness: Ways to build resilience in children - Ng, Alvin Lai Oon * (Star Media Group Berhad, 2023)
HONEST question to parents: Can your children bounce back from failures and disappointment? Do they have enough healthy behavioural, social and cognitive skills to progress, adapt and thrive? The next time your child misbehaves, instead of punishing, take a step back and think: What are the skills needed to be taught so that he or she is not likely to misbehave again? Then, focus on teaching that skill. This approach is called positive psychology – focusing on how to proactively progress the child, rather than rely on punitive action. And this is also how you build resilience in children.